FACTORS AFFECTING WOMEN’S ENROLLMENT IN CONSTRUCTION EDUCATION IN NIGERIA - Joshua Oluwasuji DADA (Journal of Construction Project Management and Innovation)
The Millennium Development Goals (MDGs) have advocated for the empowerment of women in all aspects of the economy for them to be economically self-reliant and actively participate in decision making. While the construction industry remains a major player in the economy of any nation, in Nigeria and indeed globally, the industry is male dominated. This paper reports on a study carried out on assessing factors affecting women enrolment in construction education in Nigeria. Structured questionnaires were used to collect data from targeted students, within and outside construction related-disciplines, of Obafemi Awolowo University, Ile-Ife, Nigeria. The results validate the fact that women were not at the fore front and their impact on or participation in construction sector is not been felt. Gender discrimination was also revealed as one of the problems confronting the very few women in the sector. From the trend analysis presented, it was revealed that women enrolment over the years has been extremely low as compared to that of men. The paper concludes on the need to make a concerted effort in the enhancement of women enrolment and eventual participation in construction in Nigeria.